(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the current status of sleep disorders among hospitalized patients with heart failure at the Vietnam National Heart Institute. Methods: A cross-sectional descriptive study was conducted on 186 inpatients diagnosed with heart failure at the Vietnam National Heart Institute – Bach Mai Hospital from October 2024 to April 2025. Data were collected through clinical assessments and the Pittsburgh Sleep Quality Index (PSQI). Results: A total of 62.9% of patients had heart failure classified as NYHA class III-IV, and 76.3% of patients experienced poor sleep quality (PSQI > 5). Insomnia was the most common type of sleep disorder (69.4%), followed by sleep apnea (25.3%). Notably, 52.2% of patients had very poor sleep efficiency (< 65%). This condition was more prevalent among older adults, those with lower educational attainment, advanced heart failure, and unstable income, leading to significant consequences in terms of daytime symptoms. Conclusions: Sleep disorders are highly prevalent among hospitalized heart failure patients. Routine screening and early intervention are essential to improve sleep quality and enhance disease management.